Geotechnical Analysis for Slide Dump Geometry Optimization at PT Alamjaya Bara Pratama Mine Disposal Area in Pit 4B, Kutai Kartanegara Regency - Yoga Apri Disetia; Prasetyo Wibowo; Pratama Gilang Kusuma; Faraz Sya'bana; M. Tegar Rizqullah (Pusat Publikasi Nusantara, 2024)
The management of open-pit mines is one of the challenges that often arises in the management of mine disposal areas, especially in supporting the efficiency of transporting mining materials. In this context, it is important to design a safe and efficient slide dump geometry to reduce the risk of slope failure and operational costs. The study involved the collection of geotechnical data, such as lithological and stratigraphic data obtained from exploratory drilling activities, as well as material property data, including cohesion and deep shear angle (). The collected data was then input into slope stability analysis software with the limit equilibrium method, which ultimately informed safe design recommendations for the disposal slide dump area. The results of this study not only provide an understanding of slope stability, but also highlight the importance of design optimization in supporting operational efficiency. Overall, this study confirms that the design of the disposal slides at the high wall of Pit 4B is stated to be feasible according to the calculations, simulations, and risk analysis that have been carried out, with the hope of meeting the aspects of safety, efficiency, and environmental sustainability.